2023
DOI: 10.1097/aog.0000000000005115
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Opioid-Related Mortality in Patients With Public Insurance

Abstract: Pregnant individuals with opioid use disorder have a high incidence of postpartum death due to opioid overdose, other substance-related injuries, accidents, and suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Depression in pregnancy is a significant risk factor for postpartum depression (Liu et al 2022 ), underscoring the importance of screening for and treating depression during pregnancy. In addition, a study of women with public insurance found that mental health was associated with opioid overdose deaths in the postpartum period (Suarez et al 2023 ). Further research is needed to fully understand the relationship between stigma and longer-term outcomes among pregnant women with opioid use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Depression in pregnancy is a significant risk factor for postpartum depression (Liu et al 2022 ), underscoring the importance of screening for and treating depression during pregnancy. In addition, a study of women with public insurance found that mental health was associated with opioid overdose deaths in the postpartum period (Suarez et al 2023 ). Further research is needed to fully understand the relationship between stigma and longer-term outcomes among pregnant women with opioid use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a lack of mandates for specialized SUD care, such as MOUD programs, which is notable given that opioid overdose is a significant cause of maternal mortality. 12 Evidence-based guidelines advise that pregnant persons with OUD should be on MOUD and avoid withdrawal. 13 Recent studies show that many carceral settings continue pre-incarceration MOUD in pregnancy, but few initiate MOUD and provide both methadone and buprenorphine.…”
Section: Discussionmentioning
confidence: 99%
“…3 Not only are postpartum individuals with OUD at increased risk of fatal opioid overdose, but they are also at increased risk of dying from other causes, including drug- and alcohol-related causes, suicide, homicide, and other diseases. 5…”
mentioning
confidence: 99%
“…3 Not only are postpartum individuals with OUD at increased risk of fatal opioid overdose, but they are also at increased risk of dying from other causes, including drug-and alcoholrelated causes, suicide, homicide, and other diseases. 5 In January 2023, the federal government passed the Consolidated Appropriations Act, which expanded access to OUD treatment by removing the buprenorphine DATA-Waiver requirement, also known as an X-waiver. Now any clinician with a Drug Enforcement Administration registration with Schedule III authority can prescribe buprenorphine.…”
mentioning
confidence: 99%